Study of gut microbiome and metabolomics profiling in colorectal cancer patients - Lucky Goh Poh Wah (2019)
The human gastrointestinal tract harbors millions of gut microbiota. The gut microbiota has been linked to various cancers, including gastric, liver and colorectal cancers (CRC). Despite the profound knowledge and understanding of CRC development, CRC incidence rate is increasing every year and the trend is shifting to younger age every year. This signals the need to understand the role of gut microbiota and host interactions in CRC. Therefore, this study is aimed to investigate the gut microbiota and its association to annotated host metabolites that play a potential role in the CRC with the support from gene expression analysis. A total of 35 paired case-control intestinal mucosal tissue sample were collected from CRC patients and subjected to multiple analyses. Thirty case-control tissues were subjected to gut microbiota analysis using 16S rRNA next generation sequencing. Twenty-three case-control tissues were used in metabolomics analysis using mass spectrometry. Twenty-eight case-control tissues were subjected to gene expression analysis using real-time PCR. The composition of gut microbiota, alpha diversity metrics (chaol, goods coverage, observed OTUs, Shannon index, Simpson's index, and phylogenetic distance) and beta diversity metrics (ANOSIM, PERMANOVA, PERMDISP and MRPP) shows that the gut microbiota were stable in CRC patients despite the difference in tissue pathology (cancer vs normal). Genus level analysis identified Campy/obacter from the Proteobacteria phylum was significantly (p-value < 0.05) more abundant in cases. Functional content profiling of the gut microbiota shows that glycosyltransferases, lipopolysaccharide biosynthesis proteins and its contents were also significantly (p-value < 0.05) higher in cases. Moreover, primary bile acid biosynthesis was most significantly lower (p-value < 0.05) in cases followed by bacterial toxins as well as pentose and glucuronate interconversions.